Cultural stratigraphy at Mezhirich, an Upper Palaeolithic site in Ukraine with multiple occupations - Soffer, Olga
The later Palaeolithic sites on the East European plain are celebrated for their solid buildings constructed of mammoth bones. Were these permanent settlements, occupied all the year round? Or were they seasonally occupied, in a land where winters are harsh? Stratigraphic explorations at Mezhirich, and excavation of the empty space between the buildings, leads to a decisive interpretation.